Large‐scale isolation of human skeletal muscle satellite cells from post‐mortem tissue and development of quantitative assays to evaluate modulators of myogenesis. Issue 2 (24th January 2013) - Scott, Ian C.; Tomlinson, Wendy; Walding, Andrew; Isherwood, Beverley; Dougall, Iain G.
Abstract : Background: During aging, there is a decreased ability to maintain skeletal muscle mass and function (sarcopenia). Such changes in skeletal muscle are also co‐morbidities of diseases including cancer, congestive heart failure and chronic obstructive pulmonary disease. The loss of muscle mass results in decreased strength and exercise tolerance and reduced ability to perform daily activities. Pharmacological agents addressing these pathologies could have significant clinical impact, but their identification requires understanding of mechanisms driving myotube formation (myogenesis) and atrophy and provision of relevant assays. The aim of this study was to develop robust in vitro methods to study human myogenesis. Methods: Satellite cells were isolated by digestion of post‐mortem skeletal muscle and selection using anti‐CD56 MicroBeads. CD56 + cell‐derived myotubes were quantified by high content imaging of myosin heavy chains. TaqMan‐polymerase chain reaction arrays were used to quantify expression of 41 selected genes during differentiation. The effects of activin receptor agonists and tumour necrosis factor alpha (TNFα) on myogenesis and gene expression were characterised. Results: Large‐scale isolation of CD56 + cells enabled development of a quantitative myogenesis assay with maximal myotube formation 3 days after initiating differentiation. Gene expression analysis demonstrated expression of 19 genes changed substantially during myogenesis. TNFα and activin receptor agonists inhibited myogenesis and downregulated gene expression of muscle transcription factors, structural components and markers of oxidative phenotype, but only TNFα increased expression of pro‐inflammatory markers. Conclusions: We have developed methods for large‐scale isolation of satellite cells from muscle and quantitative assays for studying human myogenesis. These systems may prove useful as part of a screening cascade designed to identify therapeutic agents for improving muscle function. Electronic supplementary material: The online version of this article (doi:10.1007/s13539‐012‐0097‐z) contains supplementary material, which is available to authorized users.